Cost-effectiveness analysis of various screening methods for osteoporosis in perimenopausal Thai women - Suthee Panichkul (2018)
Objective: perform a health economics analysis of 5 screening programs for osteoporosis in perimenopausal Thai women comparing two alternatives; without intervention and universal treatment without screening. Design: A decision analysis was performed to evaluate five screening strategies: Dual energy X-ray absorptiometry (DXA), Quantitative ultrasound sonography (QUS), risk index (clinical risk factors), two-step screening with QUS followed by DXA, and screening with risk index followed by DXA, comparing outcomes without intervention and universal treatment without screening. Results: The costs for universal treatment, screening by DXA with treatment, screening by QUS with treatment, screening by Risk index with treatment, screening by QUS and DXA with treatment, and screening by Risk index and DXA with treatment strategies to prevent one fracture were 207.82, 88.42, 147.05, 127.67, 71.33, and 60.30 USD, respectively. The cost for no intervention to prevent one fracture is 8.49 USD (1 USD = 40 Thai baht). Conclusion: At present, no intervention is the most cost effective strategy. However, screening with risk index and DXA with treatment became the most cost effective when the patients reached the postmenopausal period and had a high risk index, for which the prevalence of osteoporosis will increase. Cost effective screening guidelines still cannot be explicitly established until further data addressing the association between bone mass measurements in the hip and hip fracture risk, are available. Copyright © 2006 S. Karger AG.